THE ROLE OF URBAN AREA AS THE DETERMINANT FACTOR OF POPULATION GROWTH - Sri Rum Giyarsih; Muhammad Arif Fahrudin Alfana (Faculty of Geography, Universitas Gadjah Mada, 2013)
This research aims to (1) find the determinants for the increase of population growth rate and(2) understand the role of urban area as the pulling factor for the migrant. This research heldin Yogyakarta Special Region since the population growth has increasing during 2000-2010.Secondary data from the Bureau of Statistic (BPS) were used for the main analysis. Dataprocessing and analysis were performed by using descriptive-quantitative method.The resultof this research indicates that population growth rate in Yogyakarta Special Region isaffected by the increase of immigration from the other provinces. This migration is referred tothe recent migration, in which people entering this province as motivated by educational,family, sense of security, tourism, and job seeking background. This research also revealsthat Yogyakarta City and Sleman Regency becomes the center for pulling the migrant. This isespecially due to its function as the base for economy, educational city, area with stablesecurity, and low cost of living.